Implementasi Program Keputrian dalam Membentuk Akhlak Perempuan Salihah - Pebiyanti, Lilis Ariska; Romelah, Romelah; Mardiana, Dina (Fitrah: Journal of Islamic Education, 2023)
The current reality is that many Muslim women students have not reflected commendable behavior and moral deterioration is increasingly insurmountable. Character building should consider gender, because the basic behavior of a person is not the same. With regard to that, this study aims to analyze the women's program in shaping the morals of female students to become salihah women and its implementation at SMP Muhammadiyah 1 Malang City. The focus of the study is on learning materials and implementation. The research method used is qualitative with a case study approach. This research was conducted at SMP Muhammadiyah 1 Malang City. The research informants were the vice principal of student affairs, the coordinating teacher, the teacher presenting the material and the female students. While the data collection method uses observation, interviews and documentation. Data analysis techniques used pattern matching, explanation making and time series analysis. The results of this study indicate that the keputrian program at SMP Muhammadiyah 1 Malang City is a solution to overcome the disorientation of the behavior of Muslim teenagers today, through providing material related to religion and femininity by understanding the obligations of being a salihah woman such as covering the aurat, speaking and having good morals.